2019
DOI: 10.2340/16501977-2551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of patient education and physical training on quality of life and physical exercise capacity in patients with paroxysmal or persistent atrial fibrillation: A randomized study

Abstract: Atrial fibrillation is the most common cardiac arrhythmia and the number of atrial fibrillation patients is growing worldwide. In addition to an increase in risk of stroke and heart failure patients with atrial fibrillation also experience decrease in fitness and quality of life. In our study 58 atrial fibrillation patients draw lots to participate or not in a rehabilitation program with education and exercise training in addition to usual treatment. We measured fitness by a bicycle test at the beginning of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(62 citation statements)
references
References 27 publications
1
54
0
Order By: Relevance
“…The effect of physical exercise on cardiopulmonary fitness was measured by the peak VO 2 and resting heart rate. Four RCTs (Malmo et al, 2016 ; Risom et al, 2017 ; Joensen et al, 2019 ; Kato et al, 2019 ) reported peak VO 2 values, which were improved after physical exercise in AF patients (SMD = 0.37, 95%CI: 0.16–0.57; p < 0.001) ( Figure 7 ) with low heterogeneity ( I 2 = 0.0%, p = 0.597). Five RCTs (Osbak et al, 2012 ; Malmo et al, 2016 ; Wahlstrom et al, 2017 ; Wahlström et al, 2020 ; Kato et al, 2019 ) reported resting heart rates, which were reduced after physical exercise in AF patients (SMD = −0.39, 95%CI: −0.65 to −0.13; p = 0.004) ( Figure 8 ) with low heterogeneity ( I 2 = 23.5%, p = 0.265).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of physical exercise on cardiopulmonary fitness was measured by the peak VO 2 and resting heart rate. Four RCTs (Malmo et al, 2016 ; Risom et al, 2017 ; Joensen et al, 2019 ; Kato et al, 2019 ) reported peak VO 2 values, which were improved after physical exercise in AF patients (SMD = 0.37, 95%CI: 0.16–0.57; p < 0.001) ( Figure 7 ) with low heterogeneity ( I 2 = 0.0%, p = 0.597). Five RCTs (Osbak et al, 2012 ; Malmo et al, 2016 ; Wahlstrom et al, 2017 ; Wahlström et al, 2020 ; Kato et al, 2019 ) reported resting heart rates, which were reduced after physical exercise in AF patients (SMD = −0.39, 95%CI: −0.65 to −0.13; p = 0.004) ( Figure 8 ) with low heterogeneity ( I 2 = 23.5%, p = 0.265).…”
Section: Resultsmentioning
confidence: 99%
“…The 12 RCTs included 819 patients (408 allocated to experimental groups and 411 allocated to control groups). Four RCT exercise interventions were aerobic (Osbak et al, 2012 ; Malmo et al, 2016 ; Joensen et al, 2019 ; Nourmohammadi et al, 2019 ), one was anaerobic (Zeren et al, 2016 ), three were aerobic combined with anaerobic (Hegbom et al, 2007 ; Risom et al, 2016 ; Kato et al, 2019 ), one was Qigong (Pippa et al, 2007 ), and three were Yoga (Lakkireddy et al, 2013 ; Wahlstrom et al, 2017 ; Wahlström et al, 2020 ). The details of all included studies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More research is needed to target interventions for high- patients, thereby addressing disparities. Targeted rehabilitation programs, including group education and physical training for patients with AF, significantly diminished the risk of mortality and cardiovascular hospitalizations [ 39 , 40 ]. These structured care programs have enhanced patient outcomes among patients with AF Reinforced, targeted, in-person education can improve quality of life, symptoms improvement, and medication adherence [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Several research trials implementing exercise training have reported improvements in cardiorespiratory fitness (CRF) in patients with AF (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). CRF independently predicts AF recurrence (17) and prognosis (18,19); every 1 metabolic equivalent (MET; i.e.…”
Section: Introductionmentioning
confidence: 99%